1986
DOI: 10.2337/diab.35.3.311
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Deactivation of Proinsulin Action on Glucose Disposal and Hepatic Glucose Production in Normal Man

Abstract: We have studied the deactivation of the in vivo actions of insulin and biosynthetic human proinsulin (recombinant DNA) to stimulate the glucose disposal rate (GDR) and to inhibit hepatic glucose output (HGO) in man. Twelve healthy, lean, young subjects were studied using a modification of the euglycemic glucose clamp technique. Subjects received 4-h infusions on separate occasions of insulin (15 mU/m2/min equivalent to 0.54 microgram/m2/min) or proinsulin (2.75 micrograms/m2/min), achieving steady-state serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
3

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 0 publications
1
21
3
Order By: Relevance
“…Peripheral administration of proinsulin has been shown to exert a relatively greater effect on Ra than Rd [3,5], when compared with insulin although the differential was less than we have shown here with these insulin dimers. These observations are compatible with a mechanism dependent on molecular size as proinsulin is intermediate in molecular weight between insulin and insulin dimers.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Peripheral administration of proinsulin has been shown to exert a relatively greater effect on Ra than Rd [3,5], when compared with insulin although the differential was less than we have shown here with these insulin dimers. These observations are compatible with a mechanism dependent on molecular size as proinsulin is intermediate in molecular weight between insulin and insulin dimers.…”
Section: Discussioncontrasting
confidence: 43%
“…The most well-established quantitative data are derived from extensive studies with human proinsulin. It has been reported that proinsulin, in comparison to insulin, is more effective in the liver than in the periphery [3][4][5]. The reasons for this are not yet understood.…”
mentioning
confidence: 92%
“…Results for the control subjects are similar to those of Weiss et al and would suggest that insulin levels are indeed markedly raised in our offspring of diabetic mothers. Proinsulin and 32-33 split proinsulin have longer half-lives (23)(24)(25) and are poorer substrates for insulindegrading enzymes (26) than insulin. We have previously demonstrated that insulin propeptides are more stable in cord blood than insulin and have closer relationships to fetal growth and leptin concentrations at birth than insulin (13).…”
Section: Westgate and Associatesmentioning
confidence: 99%
“…A limitation of this study was that infants were not fasted before blood sampling. As fasting infants is unethical, we selected metabolic markers that were not very sensitive to the non-fasting state (Glauber et al,1986;Karlsson et al, 2004;Gil-Campos et al, 2010). Taken together, a high level of split proinsulin at the age of 6 months likely indicates susceptibility to adverse metabolic programming in these infants.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the infants' metabolic status, serum 32-33 split proinsulin, intact proinsulin and adiposity-derived hormones, leptin and adiponectin were chosen as metabolic markers, as these are not sensitive to the non-fasting state (Glauber et al, 1986;Karlsson et al, 2004;Gil-Campos et al, 2010) unlike blood glucose and insulin concentrations. Indeed, for obvious ethical reasons, overnight fasting was not possible at the age of 6 months.…”
Section: Samplingmentioning
confidence: 99%